Asking about content and adding content: two patterns of classroom interaction - Batavia, Edgar Lucero (Colombian Applied Linguistics Journal, 2012)
This research project focuses on identifying and describing the interactional patterns and the speech acts that emerge and are maintained through teacher-student interactions in a university-level EFL Pre-intermediate class. This work also analyzes how these patterns potentially influence the participants’ interactional behavior. This study then answers two questions: what interactional patterns emerge and how they are structured in interactions between the teacher and the students in the EFL class? And, how can the utterances that compose the interactional patterns potentially influence both interactants’ interactional behavior in the EFL class? The description and analysis of the problem follow ethnomethodological conversation analysis. The findings show that there are two main interactional patterns in the EFL class observed for this study: asking about content, and adding content. Both patterns present characteristic developments and speech acts that potentially influence the teacher and students’ interactional behavior in this class. These findings serve as a reference and evidence for the interactional patterns that emerge in EFL classroom interaction and the influence they have on the way both interactants use the target language in classroom interaction.